Study on rainfall infiltration characteristics and instability mechanism of a lateritic soil landslide in Yunnan, China - Gu, Chuan; Chen, Liang; Zuo, Weizhong; Li, Weile; Man, Hao; Lu, Hanyu; Ji, Feng (Frontiers in Earth Science, 2024)
IntroductionThe engineering geological characteristics of Yunnan’s lateritic soil are quite unique, making it prone to shallow group landslides under rainfall conditions. This study focused on an old lateritic soil landslide as a case study.MethodsSoil column ponding infiltration experiment was conducted to investigate the infiltration behavior of the lateritic soil. Numerical simulation software was employed to analyze the rainfall-induced seepage characteristics of the landslide, and a comprehensive assessment of the failure mechanisms of the lateritic soil landslide was conducted.ResultsThe study findings are as follows: (1) During water infiltration, the infiltration time curve of the lateritic soil column showed a parabolic growth trend. The migration rate of the wetting front rapidly decreased from 0.15 to 0.2 cm/min to 0.1 cm/min and then stabilized at approximately 0.04 cm/min. (2) Long-term heavy rainfall is the condition for the formation of this old lateritic soil landslide. By coupling the seepage process, the stability coefficient of the lateritic soil slope was calculated, revealing that the instability rainfall threshold of the slope under prolonged rainfall conditions is generally 120 mm/d. (3) The main changes in the seepage field occurred in the shallow soil layer. In the later stages of rainfall, the infiltration rate of the slope was controlled by the permeability coefficient of the lateritic soil. As the rainfall intensity increased, the depth of rainfall impact increased, and the pore water pressure in the shallow soil layer tended to gradually increase and then stabilize under different rainfall intensities. (4) Under long-term rainfall conditions, the volumetric water content of the soil at the toe of the lateritic soil slope first peaked. After the rainfall ended, moisture in the slope continued to migrate to the toe, keeping the soil at the toe in a saturated state. (5) The formation and evolution of this lateritic soil landslide could be divided into five stages: initial natural stage, rainfall infiltration-crack expansion, shallow creep-progressive collapse of the front edge, sliding surface penetration-overall instability, and landslide braking accumulation.ConclusionThe research results provide significant theoretical guidance and practical implications for understanding the causes and prevention of lateritic soil landslides in similar areas.